FAKTOR-FAKTOR YANG MEMPEGARUHI KINERJA KEUANGAN PERBANKAN DI INDONESIA - Farah Margaretha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
This study aimed to analyze the factors affecting financial performance in the banking industry in Indonesia. This study uses secondary data, where sampling is composed of all banks listed on the Indonesia Stock Exchange during the period of 6 years, from 2010-2015. The type of data in this research is the method of data analysis used is Multiple Regression. The results of hypothesis testing showed positive significant effect between size and capital to all variables financial performance of banks in Indonesia. The influence of positive signikan between efficiency and risk to ROA and ROE., negative signikan between efficiency and risk to NIM and LIQ, positive signikan between inflation and the business cycle of the ROA and ROE, negative signikan between inflation and the business cycle of the NIM and LIQ. The implications of this research to improve the performance of banks, such as raising capital because it could be one way of banks to expand, increasing the size, reduce operational costs, optimize the total banking assets, optimize total and reduce and the investor as consideration in investing in the banking industry, we recommend that investors need to consider capital, the size (size) and the risk that banks will be invested.Â